Adept „szkoły Naruszewicza”. Kilka uwag o stylu poezji Franciszka Zabłockiego - Szymor-Rólczak, Marta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
In the light of hitherto studies, Franciszek Zabłocki is perceived as a not fully independentpoet, who willingly used stylistic patterns borrowed from his mentors – Adam Naruszewicz andIgnacy Kraszewski. However, detailed information regarding stylistic borrowings are difficult tofind. The article is fully devoted to the above issue. It deals respectively with such concerns as:coexistence of the founders of the aforementioned “Naruszewicz’s school” in the poetry, whichmeans, also of Zabłocki himself, as well as baroque and classicist style, new formed words:compound words, rhetoric figures, allegoric images, animizations and personifications, syntacticinversion, tendency to pointing and applying proverbs and common sayings in poetry.